Ccl5 Mediates Proper Wiring of Feedforward and Lateral Inhibition Pathways in the Inner Retina - Duncan, D’Anne S.; Weiner, Rebecca L.; Weitlauf, Carl; Risner, Michael L.; Roux, Abigail L.; Sanford, Emily R.; Formichella, Cathryn R.; Sappington, Rebecca M. (Frontiers in Neuroscience, 2018)
The β-chemokine Ccl5 and its receptors are constitutively expressed in neurons of the murine inner retina. Here we examined the functional and structural significance of this constitutive Ccl5 signaling on retinal development. We compared outcomes of electrophysiology, ocular imaging and retinal morphology in wildtype mice (WT) and mice with Ccl5 deficiency (Ccl5-/-). Assessment of retinal structure by ocular coherence tomography and histology revealed slight thinning of the inner plexiform layer (IPL) and inner nuclear layer (INL) in Ccl5-/- mice, compared to WT (p < 0.01). Assessment of postnatal timepoints important for development of the inner nuclear layer (P7 and P10) revealed Ccl5-dependent alterations in the pattern and timing of apoptotic pruning. Morphological analyses of major inner retinal cell types in WT, Ccl5-/-, gustducingfp and gustducingfp/Ccl5-/- mice revealed Ccl5-dependent reduction in GNAT3 expression in rod bipolar cells as well as a displacement of their terminals from the IPL into the GCL. RGC dendritic organization and amacrine cell morphology in the IPL was similarly disorganized in Ccl5-/- mice. Examination of the intrinsic electrophysiological properties of RGCs revealed higher spontaneous activity in Ccl5-/- mice that was characterized by higher spiking frequency and a more depolarized resting potential. This hyperactive phenotype could be negated by current clamp and correlated with both membrane resistance and soma area. Overall, our findings identify Ccl5 signaling as a mediator of inner retinal circuitry during development of the murine retina. The apparent role of Ccl5 in retinal development further supports chemokines as trophic modulators of CNS development and function